2011
DOI: 10.2217/clp.11.12
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of dendritic cell function by PGE2 and DHA: a framework for understanding the role of dendritic cells in neuroinflammation

Abstract: Neuroinflammation characterizes various neurological disorders. Peripheral immune cells and CNS-resident glia contribute to neuroinflammation and impact CNS degeneration, recovery and regeneration. Recently, the role of dendritic cells in neuroinflammation received special attention. The function of infiltrating immune cells and resident glia is affected by various factors, including lipid mediators. Polyunsaturated fatty acids, especially n-6 arachidonic acid and n-3 docosahexaenoic acid (DHA), the most abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 144 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…Although the actions of RvD1 on DCs and T cells are not yet studied, 54 the RvD1 precursor DHA leads to reduction of costimulatory molecules and cytokine production in human monocyte-derived DCs and murine BMDCs. 51,[55][56][57] Dendritic cells treated with DHA show reduced ability to activate naive T cells to differentiate into Th1/Th17 effectors in an experimental encephalitis model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the actions of RvD1 on DCs and T cells are not yet studied, 54 the RvD1 precursor DHA leads to reduction of costimulatory molecules and cytokine production in human monocyte-derived DCs and murine BMDCs. 51,[55][56][57] Dendritic cells treated with DHA show reduced ability to activate naive T cells to differentiate into Th1/Th17 effectors in an experimental encephalitis model.…”
Section: Discussionmentioning
confidence: 99%
“…13 Resolvin D1 has also been shown to limit PMN infiltration in murine peritonitis, block transendothelial migration of human PMNs, and enhance phagocytosis by human macrophages. [14][15][16][17] Although a recent report demonstrated that RvD1 promotes clearance of allergens in asthma 18 and resolvin E1 (RvE1) reduces dendritic cell (DC) migration and IL-12 production, 19,20 the function of RvD1 in adaptive immune responses remains largely unexplored.…”
mentioning
confidence: 99%
“…PGE2 derived from COX-2 promotes the growth of CRC via the activation of epidermal growth factor receptor (EGFR) signaling [ 10 , 114 ]. In myeloid DCs differentiated from bone marrow, PGE2 is important in modulating the secretion of cytokines such as TNF-α, IL-6 and IL-23 by reorienting the cell’s differentiation and maturation [ 118 ]. Multiple studies reported the inhibition of DCs’ function by PGE2 [ 118 , 119 , 120 ].…”
Section: Lipid Molecule Pge2mentioning
confidence: 99%
“…IL-17 can also induce other proinflammatory mediators besides cytokines and chemokines (Table 1). IL-17 can induce NOS and PGE2 production by various cell types [12,[19][20][21], and these mediators are involved in the production of proinflammatory cytokines, in the regulation of immune cell differentiation [22-25] and have been implicated in the pathogenesis of several autoimmune diseases including RA [23, [26][27][28]. IL-17 also induces components of the complement systems such as C3 and factor B [29,30] and mediators of the innate immune systems such as the TLRs [31], all 60,87,89,90,93] implicated in the pathogenesis of RA [32][33][34].…”
Section: Effect Of Il-17 On Inflammatory Mediators and Their Regulatorsmentioning
confidence: 99%